2008
DOI: 10.1179/joc.2008.20.4.503
|View full text |Cite
|
Sign up to set email alerts
|

FOLFOX2 in the Treatment of Advanced Colorectal Cancer: A Comparison Between Elderly and Middle Aged Patients

Abstract: The effectiveness of chemotherapy in elderly patients is still a matter of debate. We analyzed the toxicity and efficacy of the original FOLFOX2 regimen in middle aged and elderly patients affected by metastatic colorectal cancer. Consecutive patients with metastatic CRC and measurable disease were eligible. Seventy-eight partially pretreated patients were enrolled: 58 patients were defined as middle aged (<70 years) and 20 were elderly patients (>70 years). Elderly patients in comparison to middle-aged patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The majority of data currently available in the literature come from retrospective analyses of Phase III studies on metastatic disease, in which it has been observed that some participants initially treated with palliative therapy became susceptible to radical resection of their hepatic metastases . Moreover, many studies have demonstrated that the use of antiblastic chemotherapy in the older adults with CRC is safe and feasible, especially in those with good performance status …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of data currently available in the literature come from retrospective analyses of Phase III studies on metastatic disease, in which it has been observed that some participants initially treated with palliative therapy became susceptible to radical resection of their hepatic metastases . Moreover, many studies have demonstrated that the use of antiblastic chemotherapy in the older adults with CRC is safe and feasible, especially in those with good performance status …”
Section: Discussionmentioning
confidence: 99%
“…Few data are available on the use of antiblastic chemotherapy in the neoadjuvant setting for liver colorectal metastases; conversely, many studies have demonstrated that chemotherapy can be safely used in older adults with metastatic CRC …”
mentioning
confidence: 99%
“…77,81,85,93 Elderly patients also experienced higher toxicity in 6/19 studies (32%) 71,85,98 but not significantly different in 13/19 studies (68%), 40,70,72,73,75,77,[82][83][84]86,89,91,92 and, more hospitalizations in 2 reporting studies (100%). 85,91 The key chemotherapy outcomes were that elderly patients experienced:worse overall response rate in 1/13 studies (8%) 71 but not significantly different in 12/13 studies (92%), 70,74,75,77,78,[82][83][84]86,87,89,92 worse overall survival in 7/24 studies (29%) 6,40,78,84,[96][97][98] and not significantly different in 17/24 studies (71%), 71,[73][74][75]77,[79]…”
Section: Chemotherapy For Hepatic and Pulmonary Crc Metastases Detect...mentioning
confidence: 93%
“…85,91 The key chemotherapy outcomes were that elderly patients experienced:worse overall response rate in 1/13 studies (8%) 71 but not significantly different in 12/13 studies (92%), 70,74,75,77,78,[82][83][84]86,87,89,92 worse overall survival in 7/24 studies (29%) 6,40,78,84,[96][97][98] and not significantly different in 17/24 studies (71%), 71,[73][74][75]77,[79][80][81][82][83]86,87,[89][90][91][92]95 and interestingly, progression-free survival for elderly patients was significantly better in 2/20 studies (10%) 86,87 but worse in 2/20 studies (10%) 96,97 and not significantly different in 16/20 studies (80%). 40,71,[73][74][75]…”
Section: Chemotherapy For Hepatic and Pulmonary Crc Metastases Detect...mentioning
confidence: 97%
See 1 more Smart Citation